Rapid Enabling of Gluconobacter oxydans Resistance to High D-Sorbitol Concentration and High Temperature by Microdroplet-Aided Adaptive Evolution - Liu, Li; Zeng, Weizhu; Yu, Shiqin; Li, Jianghua; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2021)
Gluconobacter oxydans is important in the conversion of D-sorbitol into L-sorbose, which is an essential intermediate for industrial-scale production of vitamin C. In a previous study, the strain G. oxydans WSH-004 could directly produce 2-keto-L-gulonic acid (2-KLG). However, its D-sorbitol tolerance was poor compared with that of other common industrial G. oxydans strains, which grew well in the presence of more than 200 g/L of D-sorbitol. This study aimed to use the microbial microdroplet culture (MMC) system for the adaptive evolution of G. oxydans WSH-004 so as to improve its tolerance to high substrate concentration and high temperature. A series of adaptively evolved strains, G. oxydans MMC1-MMC10, were obtained within 90 days. The results showed that the best strain MMC10 grew in a 300 g/L of D-sorbitol medium at 40°C. The comparative genomic analysis revealed that genetic changes related to increased tolerance were mainly in protein translation genes. Compared with the traditional adaptive evolution method, the application of microdroplet-aided adaptive evolution could improve the efficiency in terms of reducing time for strain evolution and simplifying the procedure, indicating that the microdroplet-aided adaptive evolution was an effective tool in improving the phenotypes with undemonstrated genotypes in a short time.